E-LEARNING PLATFORMS IN ROMANIAN HIGHER EDUCATION - LUCIAN LUPU DIMA; EDUARD EDELHAUSER; ANDREEA IONICĂ (Annals of the University of Petrosani: Economics)
Master’s Degree Programs generally use specific e-learning methods as a complementary training. The University of Petrosani has a partnership with Siveco Romania in the IT field focusing on ERP systems and on e-learning platforms through AeL product. We selected two Master’s Degree programmes due to the qualifications it provided on the labour market, for implementing an online master. The design of master’s degree academic curricula in e-learning system will involve the curricular development, the designing of the learning resources with the help of the e-learning technology as well as the development and simulation of the instructive-educational web-based process; all these aspects using AeL which is a universal and integrated e-learning solution, offering facilities for the management and presentation of various types of educational content, such as multimedia interactive materials, simulations, and tests, covering a wide range of subjects.